Assessing Crop Water Demand and Deficit for the Growth of Spring Highland Barley in Tibet, China - Zhao-fei LIU; Zhi-jun YAO; Cheng-qun YU; Zhi-ming ZHONG (Journal of Integrative Agriculture, 2013)
The aim of this study was to assess the crop water demand and deficit of spring highland barley and discuss suitable irrigation systems for different regions in Tibet, China. Long-term trends in reference crop evapotranspiration and crop water demand were analyzed in different regions, together with crop water demand and deficit of spring highland barley under different precipitation frequencies. Results showed that precipitation trends during growth stages did not benefit the growth of spring highland barley. The crop coefficient of spring highland barley in Tibet was 0.87 and crop water demand was 389.0 mm. In general, a water deficit was found in Tibet, because precipitation was lower than water consumption of spring highland barley. The most severe water deficit were in the jointing to heading stage and the heading to wax ripeness stage, which are the most important growth stages for spring highland barley; water deficit in these two stages would be harmful to the yield. Water deficit showed different characteristics in different regions. In conclusion, irrigation systems may be more successful if based on an analysis of water deficit within different growth stages and in different regions.